Principles and reactions : chemistry for engineering students - Masterton, William L.; Hurley, Celine N. ;Peterson, James F. ;Sack, Dorothy ;Gabler, Robert E. (Singapore : Cengage Learning Asia Pte Ltd, 2018)
Appropriate for either a one- or two-semester course, this text covers the basics of chemistry without sacrificing the essentials.
1. Matter and Measurements. -- 2. Atoms, Molecules, and Ions. -- 3. Mass Relations in Chemistry Stoichiometry -- 4. Reactions in Aqueous Solution. -- 5. Gases. -- 6. Electronic Structure and the Periodic Table. -- 7. Covalent Bonding. -- 8. Thermochemistry. -- 9. Liquids and Solids. -- 10. Solutions. -- 11. Rate of Reaction. -- 12. Gaseous Chemical Equilibrium. -- 13. Acids and Bases. -- 14. Equilibria in Acid-Base Solutions. -- 15. Complex Ions. -- 16. Precipitation Equilibria. -- 17. Spontaneity of Reaction. -- 18. Electrochemistry. -- 19. Nuclear Reactions. -- 20. Chemistry of the Metals. -- 21. Chemistry of the Non metals. 22. Organic Chemistry. -- 23. Organic Polymers, Natural and Synthetic. -- 24. Soils and Soil development.
Includes index.
Keywords: CHEMISTRY